La extradición y la cooperación internacional. Falta de justicia, legitimidad o incapacidad del Estado colombiano: su historia (2018)
Extradition is the most important judicial figure in international cooperation; the most notable cases being terrorism, drug trafficking, money laundering, weapons, trafficking in persons, criminal organizations and other punishable conducts related to the above, as well as the crimes contained in the Rome Statute. This cooperation figure in some estates has overcome a series of political, economic, legal and social barriers, becoming a more viable and more valid institution, since it has gone from being a government policy to being a state policy, in addition to extending its scope of applicability, going from the simple referral of criminals to reciprocity of information, investigation, judicial assistance, among others. Thus, countries today have the international obligation to make and ratify treaties where mutual assistance commitments are generated in the field of international cooperation, based on the principle or Latin formula called: aut dedere aut judicare (extradite or judge), issued since the Geneva Conventions of 1949, so that if the state is unable to prosecute the offender or wishes to surrender it to the requesting nation, the offender may be prosecuted by the petitioner.It is to be clarified that this regulation was set aside for decades and has its legal reappearance in articles 8 and 9 of the draft code of crimes against the peace and security of mankind of 1996, where this principle and that of the universal jurisdiction were timidly addressed. This was taken up again in 1998 when the Rome Statute of the International Criminal Court was adopted.